Problem-solving skills and self-efficacy in biology education: A systematic review - Abdul Rofi; Zaenal Abidin (Biosfer: Jurnal Pendidikan Biologi, 2026)
The study aims to analyze how both constructs have been investigated in empirical research, the reported relationships between them, the educational levels at which they are studied, and the methodological approaches and instruments employed. A systematic literature review (SLR) combined with bibliometric analysis was used as the method to provide a comprehensive overview of research trends, thematic clusters, and conceptual structures. Articles published between 2015 and 2025 in the Scopus database were screened and selected following PRISMA guidelines, resulting in seven studies that met the inclusion criteria. The bibliometric analysis identified five main thematic clusters, indicating the interaction between cognitive, affective, social, and pedagogical dimensions. The review shows that problem-solving skills are predominantly treated as indicators of cognitive achievement, while self-efficacy is positioned as a separate affective factor. Only two studies explicitly examined the relationship between these variables, reporting positive and mutually reinforcing interactions, whereas most studies analyzed them independently. Quantitative approaches with experimental or quasi-experimental designs dominated, with cognitive aspects assessed through performance tests and self-efficacy measured via Likert-scale questionnaires. Overall, the findings highlight the limited integration of cognitive–affective constructs in biology education research and emphasize the need for conceptual and methodological models that capture the dynamic interplay between self-efficacy and problem-solving performance. These insights provide implications for designing holistic and developmentally appropriate learning interventions in biology education